An automated quasi-continuous capillary refill timing device - Blaxter, L.L.; Morris, David E.; Crowe, John A.; Henry, C.; Hill, Stephen J.; Sharkey, Don; Vyas, H.; Hayes-Gill, Barrie R. (IOP Publishing, 2015)
Capillary refill time (CRT) is a simple means of cardiovascular assessment which is widely used in clinical care. Currently, CRT is measured through manual assessment of the time taken for skin tone to return to normal colour following blanching of the skin surface. There is evidence to suggest that manually assessed CRT is subject to bias from ambient light conditions, a lack of standardisation of both blanching time and manually applied pressure, subjectiveness of return to normal colour, and variability in the manual assessment of time. We present a novel automated system for CRT measurement, incorporating three components: a non-invasive adhesive sensor incorporating a pneumatic actuator, a diffuse multi-wavelength reflectance measurement device, and a temperature sensor; a battery operated datalogger unit containing a self contained pneumatic supply; and PC based data analysis software for the extraction of refill time, patient skin surface temperature, and sensor signal quality. Through standardisation of the test, it is hoped that some of the shortcomings of manual CRT can be overcome. In addition, an automated system will facilitate easier integration of CRT into electronic record keeping and clinical monitoring or scoring systems, as well as reducing demands on clinicians. Summary analysis of volunteer (n = 30) automated CRT datasets are presented, from 15 healthy adults and 15 healthy children (aged from 5 to 15 years), as their arms were cooled from ambient temperature to 5°C. A more detailed analysis of two typical datasets is also presented, demonstrating that the response of automated CRT to cooling matches that of previously published studies.